Filtrate reducer for drilling fluid and preparation method of filtrate reducer

By using polymers such as acrylamide and components such as phenolic composite crosslinking agents in the drilling fluid, and combining them with hybrid zirconium diboride whiskers and polyvinyl alcohol, a high-temperature stable and salt-resistant filter loss-reducing agent is prepared, which solves the problem of failure of the existing technology in high-temperature and high-salt environments and meets the needs of deep drilling.

CN119529784APending Publication Date: 2025-02-28CHENGDU HUINENG HENGYUAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411437901.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing filter reduction agent for drilling fluid fails in high temperature and high salt environments and cannot meet the needs of deep drilling.

Method used

A polymer including acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N-vinylpyrrolidone and acryloyloxyethyltrimethylammonium chloride are used to form a quaternary copolymer through the synergistic action of the phenolic composite crosslinking agent and the zirconium salt crosslinking agent, and combined with hybrid zirconium diboride whiskers and polyvinyl alcohol to prepare a filter reduction agent with high temperature stability and salt resistance.

Benefits of technology

The filter reduction agent still maintains good anti-filtration performance at high temperature of 220°C, and shows significant stability in saturated NaCl and high content of Ca2+ and Mg2+ environments, meeting the needs of deep drilling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a fluid loss additive for drilling fluid and a preparation method thereof, and relates to the technical field of fluid loss reduction of drilling fluid. The invention relates to a filtrate reducer for drilling fluid. Comprising the following components in percentage by weight: 7%-15% of acrylamide, 4%-8% of 2-acrylamide-2-methylpropanesulfonic acid, 4%-8% of N-vinyl pyrrolidone, 2%-6% of acryloyloxyethyl trimethyl ammonium chloride, 0.8%-1.6% of a phenolic aldehyde composite cross-linking agent, 0.2%-0.8% of a zircon salt cross-linking agent, 0.1%-0.6% of an initiator, 0.3%-0.9% of an emulsifier and the balance of water. 3%-8% of hybrid zirconium diboride whiskers, 6%-16% of polyvinyl alcohol and the balance of water. The filtrate reducer disclosed by the invention can be firmly adsorbed with clay particles, shows good high-temperature and high-salt resistance and filtrate reduction performance, can resist the temperature up to 220 DEG C, can resist NaCl to be saturated, can resist Mg < 2 + > up to 20000 mg / L or above, and can resist Ca < 2 + > up to 40000 mg / L or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of drilling fluid loss reduction, and in particular to a drilling fluid loss reducer and a preparation method thereof. Background Art

[0002] During the drilling process, due to the effect of pressure difference, the water in the drilling fluid will inevitably filter through the well wall into the formation, causing the drilling fluid to lose water. As the water enters the formation, the clay particles in the drilling fluid adhere to the well wall to form a "filter cake", forming a filter cake well wall. Since the filter cake well wall is much denser than the original well wall, it prevents the further loss of drilling fluid on the one hand, and protects the well wall on the other hand. However, if the drilling fluid loss is too large, it is easy to cause shale expansion and collapse, resulting in instability of the well wall. In addition, as the loss increases, the filter cake thickens, the well diameter decreases, causing a large torque to the rotating drill bit, causing pumping and pressure fluctuations when drilling, and easily causing differential pressure sticking. Therefore, it is necessary to add a fluid loss reducer to the drilling fluid to control the loss of drilling fluid. At present, fluid loss reducers are roughly divided into cellulose, starch, humic acid, resin and synthetic copolymer. Among them, synthetic copolymer fluid loss reducers have the advantages of good high temperature stability, multiple functions, strong adaptability and low pollution. However, with the development of conventional oil and gas resources, they are gradually depleted, prompting drilling work to invest in deep stratum oil and gas resources. The oil and gas resources are buried deep, the geothermal gradient is large, the wellbore temperature exceeds 170°C, and under the influence of high temperature, it is difficult for the fluid loss reducer molecules to be stably adsorbed on the clay surface; and the mineralization of the drilled strata is high and the composition is complex. Ca 2+ Mg 2+ High-valent metal ions such as ions react with polymer chemicals in drilling fluids, causing irreversible changes and destruction of molecular chains and functional groups, affecting their efficacy, leading to drastic changes in the rheology and filtration loss of drilling fluids. This destructive effect is more serious at high temperatures. Therefore, traditional filtration loss reducers can no longer meet the needs of safe drilling, and it is urgent to develop a high-temperature and salt-resistant filtration loss reducer to deal with the pollution of salt-gypsum layers and high-valent metal ions on drilling fluids at high temperatures. Summary of the invention

[0003] The main purpose of the present application is to provide a drilling fluid fluid loss reducer and a preparation method thereof, aiming to solve the technical problem that the high temperature and salt resistance of the existing drilling fluid fluid loss reducer cannot meet the actual needs.

[0004] To achieve the above-mentioned purpose, the present application proposes a fluid loss reducer for drilling fluid, which comprises the following components, by mass percentage: 7%-15% acrylamide, 4%-8% 2-acrylamide-2-methylpropane sulfonic acid, 4%-8% N-vinyl pyrrolidone, 2%-6% acryloyloxyethyl trimethyl ammonium chloride, 0.8%-1.6% phenolic composite crosslinking agent, 0.2%-0.8% zirconium salt crosslinking agent, 0.1%-0.6% initiator, 0.3%-0.9% emulsifier, 3%-8% hybrid zirconium diboride whisker and 6%-16% polyvinyl alcohol, and the balance is water.

[0005] Optionally, the phenolic composite cross-linking agent includes urotropine, catechol and o-phenylenediamine;

[0006] Wherein, the mass ratio of urotropine, catechol and o-phenylenediamine is (1-3):(1-2):(1-1.5).

[0007] Optionally, the zirconium salt cross-linking agent is zirconium oxychloride.

[0008] Optionally, the hybrid component in the hybrid zirconium diboride whisker is octavinyl octaaminopropyl cage-like polysilsesquioxane.

[0009] Optionally, the preparation step of the hybrid zirconium diboride whisker comprises:

[0010] The zirconium diboride whiskers are subjected to ultrasonic dispersion treatment in acetone, the ultrasonic frequency is 50 MHz to 200 MHz, and the ultrasonic time is 10 min to 25 min to obtain a zirconium diboride whisker dispersion liquid;

[0011] Octavinyl octaaminopropyl caged polysilsesquioxane is added to the zirconium diboride whisker dispersion, and reacted at 65° C.-75° C. for 6 h-12 h under a nitrogen atmosphere while stirring. After the reaction is completed, centrifugal separation is performed, and then the mixture is washed with toluene and deionized water for multiple times in sequence, and vacuum dried at 50° C.-70° C. for 4 h-6 h to obtain hybrid zirconium diboride whiskers.

[0012] Optionally, the initiator is benzoyl peroxide; and the emulsifier includes Span-80 and Tween-60.

[0013] The present application also proposes a method for preparing a fluid loss reducer for drilling fluid, comprising the following steps:

[0014] The phenolic composite crosslinking agent and the zirconium salt crosslinking agent are mixed and dissolved in water to obtain a crosslinking system;

[0015] Dissolving acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N-vinyl pyrrolidone, and acryloyloxyethyltrimethylammonium chloride in water, and adjusting the pH to 7-8 to obtain a monomer mixed solution;

[0016] Dissolve the emulsifier in the base oil, stir and mix to obtain a continuous phase;

[0017] Adding the monomer mixed solution and the cross-linking system into the continuous phase, and obtaining an inverse emulsion after emulsification and dispersion;

[0018] The reverse phase emulsion is stirred, and after heating, an inert gas is introduced to an oxygen-free state, an initiator is added, and a polymerization reaction is carried out to obtain a quaternary polymer emulsion;

[0019] A polyvinyl alcohol aqueous solution is prepared; after surface activation treatment of hybrid zirconium diboride whiskers, the hybrid zirconium diboride whiskers are added to the polyvinyl alcohol aqueous solution together with the quaternary polymer emulsion, mixed, stirred to break the emulsion, and then dried to obtain a fluid loss reducer.

[0020] Optionally, the step of stirring the inverse emulsion, heating it, introducing an inert gas to an oxygen-free state, adding an initiator, and performing a polymerization reaction to obtain a quaternary polymer emulsion comprises:

[0021] The reverse emulsion is stirred at a stirring rate of 80 r / min-120 r / min, and after the temperature is raised to 50° C.-75° C., an inert gas is introduced to an oxygen-free state, an initiator is added, and a polymerization reaction is carried out for 1 h-3 h to obtain a quaternary polymer emulsion.

[0022] Optionally, the step of performing surface activation treatment on the hybrid zirconium diboride whiskers comprises:

[0023] The hybrid zirconium diboride whiskers are immersed in a hydrofluoric acid solution for 40-60 minutes, and then ultrasonically treated in a mixed solution of sodium hydroxide and polyvinyl pyrrolidone, with an ultrasonic frequency of 50 MHz-200 MHz and an ultrasonic time of 15-30 minutes, and then washed with anhydrous ethanol and deionized water for multiple times.

[0024] Optionally, the step of stirring and demulsifying comprises:

[0025] The emulsion was broken by stirring at a stirring rate of 200 r / min-300 r / min, and after obtaining a solid product, it was transferred to anhydrous ethanol for shear washing for multiple times.

[0026] This application includes at least the following beneficial effects:

[0027] The fluid loss reducer of the present application is a quaternary copolymer formed by polymerizing acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, N-vinyl pyrrolidone and acryloyloxyethyl trimethyl ammonium chloride. Since polyacrylamide as a copolymer has poor shear stability, severe mechanical degradation during pumping, poor salt resistance and high temperature resistance, and is prone to precipitation, 2-acrylamide-2-methylpropane sulfonic acid, functional monomer vinyl pyrrolidone and cationic monomer acryloyloxyethyl trimethyl ammonium chloride are introduced on the basis of polyacrylamide. The -CC- bond is used as the main chain, and various functional monomers are grafted on the side chain. Because the breakage of the -CC- bond requires higher energy, the high-temperature stability of the polymer fluid loss reducer is better. 2-acrylamide-2-methylpropane sulfonic acid, functional monomer vinyl pyrrolidone and cationic monomer acryloyloxyethyl trimethyl ammonium chloride are introduced on the basis of polyacrylamide. As an anionic component, the sulfonic acid monomer has a strong anionic and water-soluble sulfonic acid group, which can make the main chain of the polymer molecule insensitive to the attack of divalent metal ions in the formation environment, thereby enhancing the salt resistance of the polymer. It also contains an amide group, which helps to form a hydration film, avoid the collision and aggregation of clay particles, and strengthen the protective effect of the glue; the N-vinyl pyrrolidone monomer contains a rigid five-membered heterocyclic structure, which can reduce the effect of temperature on the polymer structure and make the polymer temperature-resistant; the cationic monomer acryloyloxyethyltrimethylammonium chloride, as a cationic component, has high cationic activity and charge density. The introduction of polymer molecular side chains can improve the stability of the polymer in high temperature and high salt environments, better protect the main chain, and avoid the main chain from being degraded by heat. And the quaternary copolymer is a zwitterionic polymer, which gives it an anti-polyelectrolyte effect, thereby having better salt resistance;

[0028] The cross-linking system formed by the phenolic composite cross-linking agent and the zirconium salt cross-linking agent has high reactivity. The -CH2OH group in the phenolic composite cross-linking agent can undergo a condensation reaction with the -CONH2 of the tetrapolymer, so that the linear copolymer forms a three-dimensional network structure, and the benzene ring is embedded during the cross-linking reaction, further improving the high temperature resistance of the tetrapolymer; the zirconium salt cross-linking agent has good temperature resistance, which has both a cross-linking effect and can be firmly adsorbed on the clay end face. It can cross-link with the -CONH2 group, thereby synergistically enhancing the effect, so that the polymer molecules can be stably adsorbed on the clay surface at high temperatures;

[0029] Hybrid zirconium diboride whiskers are nano-hybrid materials. Compared with individual inorganic nanoparticles and nanopolymers, they have better dispersibility and high temperature resistance. After hybridization, the surface area of ​​zirconium diboride whiskers is further enhanced, making their lateral particle size larger and the fluid loss reduction effect better. They can firmly adhere to the surface of the well wall to form a dense and tough sheet-like structure material, thereby plugging and reducing fluid loss in micron to nanometer pores. The inorganic -Si-O-Si-structure they contain makes them highly stable in high temperature and high salt environments. At the same time, the hybrid zirconium diboride whiskers can work with zirconium salt crosslinkers to make the fluid loss agent molecules more strongly adsorbed to clay and not easy to fall off. At the same time, they can be embedded in the quaternary copolymer. Due to Ca 2+ Mg 2+ High-valent metal ions such as ions can cause acrylamide polymers to curl, and irreversibly mutate and destroy molecular chains and functional groups. However, hybrid zirconium diboride whiskers embedded in the quaternary copolymer can anchor it and protect the polymer. By anchoring the polymer, the polymer can be 2+ Mg 2+ The high-valent metal ions are not easy to curl under the action of the tetrapolymer, thus preventing the tetrapolymer from deforming and desorbing from the clay surface.

[0030] Polyvinyl alcohol has abundant hydroxyl groups, which can strengthen the hydrogen bonding effect in the network of the quaternary copolymer, thereby giving it stronger plugging ability and profile improvement ability through synergistic enhancement, so as to improve the salt resistance of the existing quaternary copolymer at high temperature and inhibit its network collapse under high calcium and magnesium conditions;

[0031] The present invention can firmly adsorb with clay particles through the synergistic effect of tetrapolymer, phenolic composite crosslinker, zirconium salt crosslinker, hybrid zirconium diboride whisker and polyvinyl alcohol, reduce filtration loss, and show good resistance to high temperature and high salt. The maximum temperature resistance can reach 220°C, the resistance to NaCl reaches saturation, and the resistance to Mg 2+ Reaching 20000mg / L or above, anti-Ca 2+ Reaching over 40000mg / L. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0033] At present, the most widely used high temperature and salt resistant fluid loss reducer in the field is mainly sulfonated phenolic resin, which has a maximum temperature resistance of 180℃ and a saturated NaCl resistance, but poor resistance to complex salts, and the agent has environmental pollution problems; while the temperature resistance of traditional environmentally friendly polymer fluid loss reducers is basically below 150℃, and the fluid loss rate in saturated NaCl salt slurry is less than 55%, and the fluid loss rate in complex salt slurry is less than 5%. However, as the drilling depth increases year by year, generally exceeding 6000m, the bottom hole temperature exceeds 160℃, and the mineralization of the drilled strata is high and the composition is complex, so higher requirements are placed on the temperature and salt resistance of the drilling fluid, and traditional fluid loss reducers cannot meet the needs of safe drilling.

[0034] In view of the technical problems existing in the prior art, an embodiment of the present application provides a fluid loss reducer for drilling fluid, which includes the following components, by mass percentage: 7%-15% acrylamide, 4%-8% 2-acrylamide-2-methylpropane sulfonic acid, 4%-8% N-vinyl pyrrolidone, 2%-6% acryloyloxyethyl trimethyl ammonium chloride, 0.8%-1.6% phenolic composite cross-linking agent, 0.2%-0.8% zirconium salt cross-linking agent, 0.1%-0.6% initiator, 0.3%-0.9% emulsifier, 3%-8% hybrid zirconium diboride whiskers and 6%-16% polyvinyl alcohol, and the balance is water.

[0035] The fluid loss reducer of the present application is polymerized by acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, N-vinyl pyrrolidone and acryloyloxyethyl trimethyl ammonium chloride to form a quaternary copolymer, which has a -CC- bond as the main chain and various functional monomers grafted on the side chain. Because the breakage of the -CC- bond requires higher energy, the high-temperature stability of the polymer fluid loss reducer is better. The 2-acrylamide-2-methylpropane sulfonic acid monomer is used as an anionic component and has a strong anionic and water-soluble sulfonic acid group, which can make the main chain of the polymer molecule invulnerable to the attack of divalent metal ions in the formation environment. Sensitive, thereby enhancing the salt resistance of the polymer, and containing amide groups, which helps to form a hydration film, prevent clay particles from colliding and aggregating, and strengthen the protective effect of the glue; N-vinyl pyrrolidone monomer contains a rigid five-membered heterocyclic structure, which can reduce the effect of temperature on the polymer structure and make the polymer temperature-resistant; cationic monomer acryloyloxyethyl trimethyl ammonium chloride as a cationic component has high cationic activity and charge density. The introduction of polymer molecular side chains can improve the stability of the polymer in a high temperature and high salt environment, better protect the main chain, and prevent the main chain from being degraded by heat. And the quaternary copolymer is a zwitterionic polymer, which gives it an anti-polyelectrolyte effect, thus having better salt resistance. The cross-linking system formed by the phenolic composite cross-linking agent and the zirconium salt cross-linking agent has high reactivity. The -CH2OH group in the phenolic composite cross-linking agent can react with the -CONH2 of the quaternary copolymer to form a three-dimensional network structure of the linear copolymer, and embed the benzene ring during the cross-linking reaction, further improving the high temperature resistance of the quaternary copolymer; the zirconium salt cross-linking agent has good temperature resistance and can be firmly adsorbed on the clay end face. It can cross-link with the -CONH2 group, thereby synergistically enhancing the effect, so that the polymer molecules can also be stably adsorbed on the clay surface at high temperatures. Hybrid zirconium diboride whiskers are nano-hybrid materials. Compared with individual inorganic nanoparticles and nanopolymers, they have better dispersibility and high temperature resistance. They can be attached to the well wall surface over a large area to form a dense and tough sheet-like structure material, thereby plugging and reducing filtration loss in micron to nanometer pores, and have strong stability in high temperature and high salt environments. At the same time, the hybrid zirconium diboride whiskers can cooperate with the zirconium salt crosslinker to make the fluid loss reducer molecules more strongly adsorbed to the clay and not easy to fall off, and have an anchoring effect on the quaternary copolymer, playing a protective role. By anchoring the quaternary copolymer, it can be 2+ Mg 2+ High-valent metal ions are not easy to curl under the action of ions, thus preventing the tetrapolymer from deforming and desorbing from the clay surface. Polyvinyl alcohol has abundant hydroxyl groups, which can strengthen the hydrogen bonding effect with the tetrapolymer network, thereby giving it stronger plugging ability and profile improvement ability through synergistic enhancement, so as to improve the salt resistance of the existing tetrapolymer at high temperature and inhibit its network collapse under high calcium and magnesium.

[0036] As an implementation method of the present application, the phenolic composite cross-linking agent includes urotropine, catechol and o-phenylenediamine;

[0037] Wherein, the mass ratio of urotropine, catechol and o-phenylenediamine is (1-3):(1-2):(1-1.5).

[0038] In specific applications, hexamethylenetetramine can be decomposed into formaldehyde and react with catechol and o-phenylenediamine to improve the reactivity of the cross-linking system. Its -CH2OH group can react with the main active group amide group (-CONH2) of the acrylamide tetrapolymer to form a three-dimensional network structure of the linear copolymer. When the tetrapolymer reacts with the phenolic composite cross-linking agent, the benzene ring is embedded, thereby further improving the high temperature resistance of the copolymer.

[0039] As an implementation method of the present application, the zirconium salt cross-linking agent is zirconium oxychloride.

[0040] Specifically, zirconium ions in zirconium oxychloride can be strongly adsorbed on the end face of clay, so that the fluid loss reducer molecules interact more strongly with the clay, are not easy to fall off, and have stronger adhesive protection ability. Zirconium oxychloride also has good temperature resistance. The polymer molecules contain a large number of amide groups, which can be used as adsorption groups. Zirconium oxychloride is used as a cross-linking agent, which can be cross-linked with -CONH2 groups, thereby synergistically enhancing the effect and making the polymer molecules stably adsorbed on the clay surface. Even in a high temperature environment, it can be firmly adsorbed on the clay surface, thereby avoiding collision and aggregation of clay particles, forming a hydration film on the clay surface, and under pressure difference, the drilling fluid solid phase accumulates to form a mud cake. The hydration film is compressed and deformed to reduce the permeability of the mud cake, thereby enhancing the fluid loss reducer effect.

[0041] As an implementation method of the present application, the hybrid component in the hybrid zirconium diboride whisker is octavinyl octaaminopropyl cage-like polysilsesquioxane.

[0042] Cage-like polysilsesquioxane is a very stable organic / inorganic hybrid nanomaterial with an inorganic core of Si-O-Si structure and a three-dimensional size between 1nm and 3nm. It is known as the "smallest silicon oxide structure". It has extremely high thermal stability, nano-size effect and good compatibility.

[0043] The present application uses octavinyl octaaminopropyl caged polysilsesquioxane as the hybrid component. In addition to the ordered cubic siloxane cage, its structure also contains eight peripheral primary amine groups, which give it excellent hydrophilicity and reactivity. Zirconium diboride whiskers are a nano-scale fiber. The strong bond between the Zr-B ionic bond and the BB covalent bond between the boron atomic plane and the zirconium atomic plane determines the high stability and high temperature resistance of this material. Due to the dense and tough characteristics of zirconium diboride whiskers, they can prevent liquid penetration and play a role in plugging and reducing filtration loss in micron to nanometer pores. However, zirconium diboride whiskers are difficult to disperse well in water-based drilling fluids. The present application uses octavinyl octaaminopropyl caged polysilsesquioxane as the hybrid component to prepare hybrid zirconium diboride whiskers. Compared with the single inorganic Nanoparticles and nanopolymers combine the inorganic properties of siloxane and the organic properties of vinyl, and have better dispersibility and high temperature resistance. After hybridization, the surface area of ​​zirconium diboride whiskers is further enhanced, making the lateral particle size larger and the fluid loss reduction effect better. They can firmly adhere to the surface of the well wall to form a dense and tough sheet-like structure material, thereby plugging and reducing the micron to nanometer pores. The inorganic -Si-O-Si-structure it contains makes it very stable in high temperature and high salt environments. At the same time, the hybrid zirconium diboride whiskers can cooperate with zirconium salt crosslinkers to make the fluid loss agent molecules more strongly adsorbed to clay and not easy to fall off. At the same time, they can be embedded in the quaternary copolymer. Due to Ca 2+ Mg 2+ High-valent metal ions such as ions can cause acrylamide polymers to curl, and irreversibly mutate and destroy molecular chains and functional groups. However, hybrid zirconium diboride whiskers embedded in the quaternary copolymer can anchor it and protect the polymer. By anchoring the polymer, the polymer can be 2+ Mg 2+ The high-valent metal ions are not easy to curl under the action of the tetrapolymer, thus preventing the tetrapolymer from deforming and desorbing from the clay surface.

[0044] As an implementation method of the present application, the preparation steps of the hybrid zirconium diboride whiskers include:

[0045] The zirconium diboride whiskers are subjected to ultrasonic dispersion treatment in acetone, the ultrasonic frequency is 50 MHz to 200 MHz, and the ultrasonic time is 10 min to 25 min to obtain a zirconium diboride whisker dispersion liquid;

[0046] Octavinyl octaaminopropyl caged polysilsesquioxane is added to the zirconium diboride whisker dispersion, and reacted at 65° C.-75° C. for 6 h-12 h under a nitrogen atmosphere while stirring. After the reaction is completed, centrifugal separation is performed, and then the mixture is washed with toluene and deionized water for multiple times in sequence, and vacuum dried at 50° C.-70° C. for 4 h-6 h to obtain hybrid zirconium diboride whiskers.

[0047] In the application, under the nitrogen atmosphere, under the electrostatic interaction between the peripheral primary amine groups and the inorganic silicon oxygen cage and the surface of the zirconium diboride whisker, the octavinyl octaaminopropyl cage-like polysilsesquioxane can be evenly distributed on the surface of the zirconium diboride whisker, thereby effectively improving the water dispersibility and stability of the zirconium diboride whisker and increasing the surface area of ​​the zirconium diboride whisker.

[0048] Specifically, the mass ratio of octavinyl octaaminopropyl cage-shaped polysilsesquioxane to zirconium diboride whisker is (1.5-2): (3.5-5.5). The diameter of the zirconium diboride whisker is 100nm-300nm, and the length is 400nm-900nm.

[0049] As an implementation method of the present application, the initiator is benzoyl peroxide; the emulsifier includes Span-80 and Tween-60. Dibenzoyl peroxide is a strong oxidant, which can be used as an initiator to initiate polymerization. Span refers to a low molecular weight polyether, which is a non-ionic surfactant. Span-80 has excellent emulsification stability and lubricity. Tween refers to polyethylene glycol-etherified octanol styrene ester and its derivatives, which are non-ionic surfactants. Tween-60 has excellent permeability and wettability and can reduce the surface tension of the liquid. Span-80 and Tween-60 act as good emulsifiers and are dispersed in the oil phase.

[0050] The embodiment of the present application also provides a method for preparing a fluid loss reducer for drilling fluid, comprising the following steps:

[0051] The phenolic composite crosslinking agent and the zirconium salt crosslinking agent are mixed and dissolved in water to obtain a crosslinking system;

[0052] Dissolving acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N-vinyl pyrrolidone, and acryloyloxyethyltrimethylammonium chloride in water, and adjusting the pH to 7-8 to obtain a monomer mixed solution;

[0053] Dissolve the emulsifier in the base oil, stir and mix to obtain a continuous phase;

[0054] Adding the monomer mixed solution and the cross-linking system into the continuous phase, and obtaining an inverse emulsion after emulsification and dispersion;

[0055] The reverse phase emulsion is stirred, and after heating, an inert gas is introduced to an oxygen-free state, an initiator is added, and a polymerization reaction is carried out to obtain a quaternary polymer emulsion;

[0056] A polyvinyl alcohol aqueous solution is prepared; after surface activation treatment of hybrid zirconium diboride whiskers, the hybrid zirconium diboride whiskers are added to the polyvinyl alcohol aqueous solution together with the quaternary polymer emulsion, mixed, stirred to break the emulsion, and then dried to obtain a fluid loss reducer.

[0057] The present application adopts an inverse emulsion polymerization method to prepare a fluid loss reducer. First, each monomer acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, N-vinyl pyrrolidone, and acryloyloxyethyl trimethyl ammonium chloride are dissolved in water to prepare an aqueous phase, and then an emulsifier is dissolved in a base oil to prepare an oil phase. The aqueous phase, the oil phase, and a cross-linking system are mixed and emulsified and dispersed to obtain an inverse emulsion, and then an initiator is used to initiate a polymerization reaction to obtain a quaternary polymer emulsion. After mixing the quaternary polymer emulsion, hybrid zirconium diboride whiskers, and polyvinyl alcohol, a fluid loss reducer with good temperature resistance and salt resistance is obtained.

[0058] Specifically, the molecular weight of the quaternary polymer is 40×10 4 -80×10 4 As the apparent viscosity of the polymer increases with the increase of molecular weight, the larger the molecular weight, the more serious the entanglement of the molecular chain, the greater the flow resistance of the polymer, and the worse the fluidity. The increase of its apparent viscosity has the effect of reducing the loss of drilling fluid and making the drilling fluid system more stable. Therefore, the molecular weight of the quaternary polymer is designed to be 40×10 4 -80×10 4 .

[0059] Specifically, the emulsifier is dissolved in the base oil at a mass ratio of 1:3, and stirred for 5 minutes at a speed of 300r / min-400r / min using a high-speed shear emulsifier; the base oil is white oil, kerosene or liquid paraffin.

[0060] Specifically, in the emulsification and dispersion step, the emulsification speed is 450 r / min-600 r / min, and the emulsification time is 20 min-40 min.

[0061] As an implementation method of the present application, the steps of stirring the inverse emulsion, heating it, introducing an inert gas to an oxygen-free state, adding an initiator, and performing a polymerization reaction to obtain a quaternary polymer emulsion include:

[0062] The reverse emulsion is stirred at a stirring rate of 80 r / min-120 r / min, and after the temperature is raised to 50° C.-75° C., an inert gas is introduced to an oxygen-free state, an initiator is added, and a polymerization reaction is carried out for 1 h-3 h to obtain a quaternary polymer emulsion.

[0063] Specifically, the inert gas may be nitrogen or argon. Since the polymerization reaction is relatively violent, the reaction conditions need to be controlled to be carried out in an oxygen-free environment, so the inert gas is introduced for at least 30 minutes to ensure that the oxygen is exhausted.

[0064] As an implementation method of the present application, the step of performing surface activation treatment on the hybrid zirconium diboride whiskers includes:

[0065] The hybrid zirconium diboride whiskers are immersed in a hydrofluoric acid solution for 40-60 minutes, and then ultrasonically treated in a mixed solution of sodium hydroxide and polyvinyl pyrrolidone, with an ultrasonic frequency of 50 MHz-200 MHz and an ultrasonic time of 15-30 minutes, and then washed with anhydrous ethanol and deionized water for multiple times.

[0066] By performing surface activation treatment on the hybrid zirconium diboride whiskers, the reaction between the hybrid zirconium diboride whiskers and the quaternary polymer can be promoted, so that the hybrid zirconium diboride whiskers are embedded in the network structure of the quaternary polymer, thereby playing an anchoring role on the quaternary polymer.

[0067] Specifically, the concentration of the hydrofluoric acid solution is 2 mL / L-6 mL / L, the mass fraction of sodium hydroxide in the mixed solution of sodium hydroxide and polyvinyl pyrrolidone is 15%-20%, and the mass fraction of polyvinyl pyrrolidone is 8%-12%.

[0068] As an implementable embodiment of the present application, the step of stirring and demulsifying includes:

[0069] The emulsion was broken by stirring at a stirring rate of 200 r / min-300 r / min, and after obtaining a solid product, it was transferred to anhydrous ethanol for shear washing for multiple times.

[0070] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0071] Example 1

[0072] A method for preparing a fluid loss reducer for drilling fluid comprises the following steps:

[0073] 12 g of a phenolic composite crosslinking agent and 5 g of a zirconium oxychloride crosslinking agent are mixed and dissolved in water to obtain a crosslinking system; wherein the phenolic composite crosslinking agent is obtained by dissolving urotropine, catechol and o-phenylenediamine in deionized water at a mass ratio of 2:1.5:1.2;

[0074] Dissolve 110 g of acrylamide, 60 g of 2-acrylamide-2-methylpropanesulfonic acid, 60 g of N-vinyl pyrrolidone, and 40 g of acryloyloxyethyltrimethylammonium chloride in water, and adjust the pH to 7 to obtain a monomer mixed solution;

[0075] Dissolve 3 g of Span-80 and 3 g of Tween-60 in 18 g of white oil, and stir at 350 r / min for 5 min using a high-speed shear emulsifier to obtain a continuous phase;

[0076] Adding the monomer mixed solution and the cross-linking system into the continuous phase for emulsification and dispersion, the emulsification speed is 520 r / min, the emulsification time is 30 min, and an inverse emulsion is obtained;

[0077] The inverse emulsion was stirred at a stirring rate of 100 r / min, and after the temperature was raised to 62° C., nitrogen was introduced to an oxygen-free state, 3 g of benzoyl peroxide was added, and a polymerization reaction was carried out for 2 hours to obtain a quaternary polymer emulsion;

[0078] After dispersing 110 g of polyvinyl alcohol in water at room temperature, the polyvinyl alcohol aqueous solution was obtained by heating and stirring to fully swell and dissolve the polyvinyl alcohol;

[0079] The zirconium diboride whiskers were subjected to ultrasonic dispersion treatment in acetone at an ultrasonic frequency of 120 MHz and an ultrasonic time of 17 minutes to obtain a zirconium diboride whisker dispersion liquid;

[0080] Adding octavinyl octaaminopropyl caged polysilsesquioxane to the zirconium diboride whisker dispersion, reacting at 70° C. for 9 hours under a nitrogen atmosphere while stirring, centrifuging after the reaction, washing with toluene and deionized water for multiple times in sequence, and vacuum drying at 60° C. for 5 hours to obtain hybrid zirconium diboride whiskers;

[0081] 50 g of hybrid zirconium diboride whiskers were soaked in a hydrofluoric acid solution with a concentration of 4 mL / L for 50 minutes, and then ultrasonically treated in a mixed solution of sodium hydroxide and polyvinyl pyrrolidone, wherein the mass fraction of sodium hydroxide was 18%, the mass fraction of polyvinyl pyrrolidone was 10%, the ultrasonic frequency was 120 MHz, and the ultrasonic time was 22 minutes. After being washed multiple times with anhydrous ethanol and deionized water in sequence, they were added into a polyvinyl alcohol aqueous solution together with a quaternary polymer emulsion, stirred and demulsified at a stirring rate of 250 r / min, and after obtaining a solid product, they were transferred to anhydrous ethanol for shear washing multiple times, and dried to obtain a filtrate reducer.

[0082] Example 2

[0083] A method for preparing a fluid loss reducer for drilling fluid comprises the following steps:

[0084] 8 g of a phenolic composite crosslinking agent and 2 g of a zirconium oxychloride crosslinking agent are mixed and dissolved in water to obtain a crosslinking system; wherein the phenolic composite crosslinking agent is obtained by dissolving urotropine, catechol and o-phenylenediamine in deionized water at a mass ratio of 1:1:1;

[0085] Dissolve 70 g of acrylamide, 40 g of 2-acrylamide-2-methylpropanesulfonic acid, 40 g of N-vinyl pyrrolidone, and 20 g of acryloyloxyethyltrimethylammonium chloride in water, and adjust the pH to 7 to obtain a monomer mixed solution;

[0086] Dissolve 1 g of Span-80 and 2 g of Tween-60 in 9 g of kerosene and stir with a high-speed shear emulsifier at a speed of 300 r / min for 5 min to obtain a continuous phase;

[0087] Adding the monomer mixed solution and the cross-linking system into the continuous phase for emulsification and dispersion, the emulsification speed is 450 r / min, the emulsification time is 40 min, and an inverse emulsion is obtained;

[0088] The inverse emulsion was stirred at a stirring rate of 80 r / min, and after the temperature was raised to 50° C., nitrogen was introduced to an oxygen-free state, 1 g of benzoyl peroxide was added, and a polymerization reaction was carried out for 1 hour to obtain a quaternary polymer emulsion;

[0089] After dispersing 60 g of polyvinyl alcohol in water at room temperature, the polyvinyl alcohol aqueous solution was obtained by heating and stirring to fully swell and dissolve the polyvinyl alcohol.

[0090] The zirconium diboride whiskers were subjected to ultrasonic dispersion treatment in acetone at an ultrasonic frequency of 50 MHz and an ultrasonic time of 25 minutes to obtain a zirconium diboride whisker dispersion liquid;

[0091] Octavinyl octaaminopropyl caged polysilsesquioxane was added to a zirconium diboride whisker dispersion, and the mixture was reacted at 65°C for 12 hours under a nitrogen atmosphere while being stirred. After the reaction was completed, the mixture was centrifuged, and then washed with toluene and deionized water for multiple times in sequence. The mixture was vacuum dried at 50°C for 6 hours to obtain hybrid zirconium diboride whiskers.

[0092] 30 g of hybrid zirconium diboride whiskers were soaked in a hydrofluoric acid solution with a concentration of 2 mL / L for 40 minutes, and then ultrasonically treated in a mixed solution of sodium hydroxide and polyvinyl pyrrolidone, wherein the mass fraction of sodium hydroxide was 15%, the mass fraction of polyvinyl pyrrolidone was 8%, the ultrasonic frequency was 50 MHz, and the ultrasonic time was 30 minutes. After being washed with anhydrous ethanol and deionized water for multiple times in sequence, they were added into a polyvinyl alcohol aqueous solution together with a quaternary polymer emulsion, stirred and demulsified at a stirring rate of 200 r / min, and after obtaining a solid product, they were transferred to anhydrous ethanol for shear washing for multiple times, and dried to obtain a filtrate reducer.

[0093] Example 3

[0094] A method for preparing a fluid loss reducer for drilling fluid comprises the following steps:

[0095] 16 g of a phenolic composite crosslinking agent and 8 g of a zirconium oxychloride crosslinking agent are mixed and dissolved in water to obtain a crosslinking system; wherein the phenolic composite crosslinking agent is obtained by dissolving urotropine, catechol and o-phenylenediamine in deionized water at a mass ratio of 3:2:1.5;

[0096] Dissolve 150 g of acrylamide, 80 g of 2-acrylamide-2-methylpropanesulfonic acid, 80 g of N-vinyl pyrrolidone, and 60 g of acryloyloxyethyltrimethylammonium chloride in water, and adjust the pH to 8 to obtain a monomer mixed solution;

[0097] Dissolve 4 g of Span-80 and 5 g of Tween-60 in 27 g of liquid paraffin, and stir for 5 min at a speed of 400 r / min using a high-speed shear emulsifier to obtain a continuous phase;

[0098] Adding the monomer mixed solution and the cross-linking system into the continuous phase for emulsification and dispersion, the emulsification speed is 600 r / min, the emulsification time is 20 min, and an inverse emulsion is obtained;

[0099] The inverse emulsion was stirred at a stirring rate of 120 r / min, and after the temperature was raised to 75° C., nitrogen was introduced to an oxygen-free state, 6 g of benzoyl peroxide was added, and a polymerization reaction was carried out for 3 hours to obtain a quaternary polymer emulsion;

[0100] After dispersing 16 g of polyvinyl alcohol in water at room temperature, the polyvinyl alcohol aqueous solution was obtained by heating and stirring to fully swell and dissolve the polyvinyl alcohol;

[0101] The zirconium diboride whiskers were subjected to ultrasonic dispersion treatment in acetone at an ultrasonic frequency of 200 MHz and an ultrasonic time of 10 minutes to obtain a zirconium diboride whisker dispersion liquid;

[0102] Adding octavinyl octaaminopropyl caged polysilsesquioxane to the zirconium diboride whisker dispersion, reacting at 75° C. for 6 hours under a nitrogen atmosphere while stirring, centrifuging after the reaction, washing with toluene and deionized water for multiple times in sequence, and vacuum drying at 70° C. for 4 hours to obtain hybrid zirconium diboride whiskers;

[0103] 80 g of hybrid zirconium diboride whiskers were soaked in a hydrofluoric acid solution with a concentration of 6 mL / L for 60 minutes, and then ultrasonically treated in a mixed solution of sodium hydroxide and polyvinyl pyrrolidone, wherein the mass fraction of sodium hydroxide was 20%, the mass fraction of polyvinyl pyrrolidone was 12%, the ultrasonic frequency was 200 MHz, and the ultrasonic time was 15 minutes. After being washed with anhydrous ethanol and deionized water for multiple times in sequence, they were added into a polyvinyl alcohol aqueous solution together with a quaternary polymer emulsion, stirred and demulsified at a stirring rate of 300 r / min, and after obtaining a solid product, they were transferred to anhydrous ethanol for shear washing for multiple times, and dried to obtain a filtrate reducer.

[0104] Comparative Example 1

[0105] Compared with Example 1, no zirconium oxychloride cross-linking agent was added, and the remaining steps remained unchanged.

[0106] Comparative Example 2

[0107] Compared with Example 1, hybrid zirconium diboride whiskers were not added, and the remaining steps remained unchanged.

[0108] Comparative Example 3

[0109] Compared with Example 1, the hybrid zirconium diboride whiskers were replaced with zirconium diboride whiskers, and the other steps remained unchanged.

[0110] Comparative Example 4

[0111] The commercially available fluid loss reducer BZ-ZNJ is a polymer-type fluid loss reducer synthesized from acrylamide, 2-acrylamide-2-methylacrylic acid and N-vinyl pyrrolidone monomers.

[0112] Comparative Example 5

[0113] Compared with Example 1, the phenolic composite cross-linking agent was replaced by urotropine, and the other steps remained unchanged.

[0114] Comparative Example 6

[0115] Compared with Example 1, the phenolic composite cross-linking agent is replaced by catechol, and the other steps remain unchanged.

[0116] Comparative Example 7

[0117] Compared with Example 1, the phenolic composite crosslinking agent is replaced by o-phenylenediamine, and the other steps remain unchanged.

[0118] Test example

[0119] The performance of the fluid loss reducers of the examples and comparative examples of the present application was tested.

[0120] 1. Foaming rate

[0121] 1.1 Base slurry preparation

[0122] Prepare 3 parts of base slurry: add 350 mL of distilled water and 12.00 g of bentonite for drilling fluid into a high-stirring cup in sequence, stir at high speed for a total of 20 minutes, interrupt at least twice to scrape off the adhesion on the cup wall, and maintain in a sealed state at room temperature for 24 hours.

[0123] 1.2 Sample slurry and determination

[0124] Take 1 portion of the base slurry prepared in 1.1, add 8.00g of the fluid loss reducer to be tested, and stir at high speed for 5 minutes to obtain the sample slurry. Start timing immediately after removing the sample slurry from the high-speed stirrer. Pour the sample slurry and foam into a clean 500mL measuring cylinder within 20 seconds, and read the total volume after 30 seconds. Calculate the foaming rate according to the following formula:

[0125]

[0126] Where:

[0127] A——foaming rate, %;

[0128] V——Total volume of sample slurry after high-speed stirring, mL.

[0129] 2. Apparent viscosity increase

[0130] Take 2 parts of the base slurry prepared in 1.1, add 12.00g of the fluid loss reducer to be tested into one part of the base slurry, which is the sample slurry, and stir it at high speed for 5 minutes with the other part of the base slurry. According to the method specified in 6.3 of GB / T 16783.1-2014, measure the viscometer readings of the base slurry and the sample slurry at 600r / min respectively. Calculate the apparent viscosity increase value according to the following formula:

[0131] ΔAV=AV2-AV1

[0132] Where:

[0133] ΔAV——apparent viscosity increase value, mPa·s;

[0134] AV1——apparent viscosity of base slurry, mPa·s;

[0135] AV2——apparent viscosity of sample slurry, mPa·s.

[0136] 3. High temperature and high pressure filtration loss

[0137] 3.1 Base slurry preparation

[0138] Prepare 4 parts of base slurry: add 350mL of distilled water and 12.00g of bentonite for drilling fluid in a high-stirring cup in sequence, stir at high speed for a total of 20 minutes, interrupt at least twice to scrape off the adhesion on the cup wall, and maintain in a sealed state at room temperature for 24 hours.

[0139] 3.2 High temperature and high pressure fluid loss in fresh water slurry

[0140] Take 1 portion of the base slurry prepared in 3.1, add 4.00g of the test fluid loss agent to be tested, that is, the sample slurry, and stir at high speed for 20 minutes. During the stirring, interrupt at least twice to scrape off the test fluid loss agent adhering to the container wall. Transfer the sample slurry to a high-temperature aging tank and roll age at 150℃ for 16 hours. Take out the high-temperature aging tank, open it after cooling, and determine the high-temperature and high-pressure filtration loss according to the method in 3.3 of GB / T16783.1-2014 (high-temperature and high-pressure conditions are: 150℃ / 3450kPa).

[0141] 3.3 High-temperature and high-pressure fluid loss in salt water slurry

[0142] Take 1 portion of the base slurry prepared in 2.1, add 12.00g of the fluid loss agent to be tested, which is the sample slurry, stir at high speed for 20 minutes, interrupt at least twice during the period to scrape off the sample adhering to the container wall, then add 14g potassium chloride, 60g magnesium chloride hexahydrate, and 40g anhydrous calcium chloride in sequence, and stir at high speed for 10 minutes. Transfer the sample slurry to a high-temperature aging tank, roll age at 150℃ for 16 hours, take out the high-temperature aging tank, open it after cooling, and determine the high-temperature and high-pressure filtration loss according to the method 3.3 in "GB / T 16783.1-2014" (high-temperature and high-pressure conditions are: 150℃ / 3450kPa).

[0143] 4. Test results

[0144] The test results are shown in Table 1 below.

[0145] Table 1

[0146]

[0147] As can be seen from Table 1, the products obtained in Examples 1 to 3 of the present application have low foaming rates and moderately increased viscosities, and are low-viscosity fluid loss reducers, indicating that they have very good fluid loss reduction capabilities in both fresh water and salt water, and their salt and calcium resistance capabilities are very outstanding;

[0148] By comparing Examples 1-3 with Comparative Example 1, it can be seen that in Comparative Example 1, since no zirconium oxychloride crosslinking agent is added, the foaming rate increases slightly, the apparent viscosity increases significantly, and the filtration loss increases significantly, indicating that the addition of zirconium oxychloride can enhance the product's ability to protect the glue, and can also be adsorbed on the surface of clay particles to form a stable hydration film through hydration, thereby increasing the system's filtration loss while also stabilizing the rheology of the slurry;

[0149] By comparing Examples 1-3 with Comparative Example 2, it can be seen that after the hybrid zirconium diboride whiskers are replaced with ordinary zirconium diboride whiskers, the foaming rate and apparent viscosity change rate of the product do not change significantly. The filtration loss increases slightly. This shows that ordinary zirconium diboride whiskers still play a certain role in protecting the glue, blocking, and synergistic cross-linking. However, since no hybrid modification was performed, the dispersibility of the product was poor, and therefore the due protective and synergistic effects in the polymer were not exerted. In Example 2, since no hybrid zirconium diboride whiskers were added, the foaming rate did not change much, and the apparent viscosity increase value was relatively reduced, but the filtration loss increased significantly, indicating that the addition of hybrid zirconium diboride whiskers can effectively improve the product's temperature resistance and salt and calcium resistance. Further analysis shows that in addition to the plugging effect of inorganic nanomaterials, hybrid zirconium diboride whiskers can also cooperate with zirconium salt crosslinking agents to make the filtration loss agent molecules more strongly adsorbed to clay and not easy to fall off. After being embedded in the quaternary copolymer, the hybrid zirconium diboride whiskers have an anchoring effect, which plays a protective effect on the glue. By anchoring the polymer, the polymer can be more easily adsorbed in Ca 2+ Mg 2+ The high-valent metal ions are not easy to curl under the action of the tetrapolymer, thus preventing the tetrapolymer from deforming and desorbing from the clay surface.

[0150] By comparing Examples 1-3 with Comparative Example 3, it can be seen that after the hybrid zirconium diboride whiskers in Comparative Example 3 were replaced with ordinary zirconium diboride whiskers, the foaming rate and apparent viscosity change rate did not change significantly, and the filtration loss increased slightly. This shows that ordinary zirconium diboride whiskers still play a certain role in protecting the glue, blocking, and synergistic cross-linking, but because no hybrid modification was performed, the dispersibility of the product was poor, and therefore it did not play the role of protecting the glue and synergistic enhancement in the polymer.

[0151] By comparing Examples 1-3 with Comparative Example 4, it can be seen that similar polymer-based fluid loss reducers currently have high foaming rates and high fluid loss amounts, indicating that the fluid loss reducer obtained by cross-linking modification and composite modification with inorganic materials in the present application has greatly improved its temperature and salt resistance;

[0152] By comparing Examples 1-3 with Comparative Examples 5, 6, and 7, it can be seen that after the phenolic composite cross-linking agent is replaced with a single cross-linking agent, the apparent viscosity of the product to which the cross-linking agent of urotropine is added alone increases greatly, and the fluid loss also increases significantly, indicating that the cross-linking effect of urotropine is stronger, excessive cross-linking occurs, and the viscosity-increasing effect of the fluid loss reducer is enhanced, while the fluid loss increases, indicating that only moderate cross-linking can help reduce the fluid loss, and excessive cross-linking will reduce the adsorption points of the product and clay particles, thereby increasing the fluid loss of the fluid loss reducer; and when a single cross-linking agent of catechol or o-phenylenediamine is added alone, the viscosity increase value decreases and the fluid loss increases, which may be because the degree of cross-linking decreases, which reduces the overall molecular weight of the fluid loss reducer, resulting in a decrease in the viscosity increase value, and the increase in the fluid loss indicates that insufficient cross-linking leads to a decrease in the temperature and salt resistance of the fluid loss reducer, mainly because insufficiently cross-linked polymer products are more likely to curl at high temperatures or high salts, and thus have insufficient temperature resistance.

[0153] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A fluid loss reducer for drilling fluid, characterized in that: The invention comprises the following components by mass percentage: 7%-15% acrylamide, 4%-8% 2-acrylamide-2-methylpropane sulfonic acid, 4%-8% N-vinyl pyrrolidone, 2%-6% acryloyloxyethyl trimethyl ammonium chloride, 0.8%-1.6% phenolic composite crosslinking agent, 0.2%-0.8% zirconium salt crosslinking agent, 0.1%-0.6% initiator, 0.3%-0.9% emulsifier, 3%-8% hybrid zirconium diboride whisker and 6%-16% polyvinyl alcohol, and the balance is water.

2. The fluid loss reducer for drilling fluid according to claim 1, characterized in that: The phenolic composite cross-linking agent includes urotropine, catechol and o-phenylenediamine; Wherein, the mass ratio of urotropine, catechol and o-phenylenediamine is (1-3):(1-2):(1-1.5).

3. The fluid loss reducer for drilling fluid according to claim 1, characterized in that: The zirconium salt cross-linking agent is zirconium oxychloride.

4. The fluid loss reducer for drilling fluid according to claim 1, characterized in that: The hybrid component in the hybrid zirconium diboride whisker is octavinyl octaaminopropyl cage-like polysilsesquioxane.

5. The fluid loss reducer for drilling fluid according to claim 1, characterized in that: The preparation steps of the hybrid zirconium diboride whiskers include: The zirconium diboride whiskers are subjected to ultrasonic dispersion treatment in acetone, the ultrasonic frequency is 50 MHz to 200 MHz, and the ultrasonic time is 10 min to 25 min to obtain a zirconium diboride whisker dispersion liquid; Octavinyl octaaminopropyl caged polysilsesquioxane is added to the zirconium diboride whisker dispersion, and reacted at 65° C.-75° C. for 6 h-12 h under a nitrogen atmosphere while stirring. After the reaction is completed, centrifugal separation is performed, and then the mixture is washed with toluene and deionized water for multiple times in sequence, and vacuum dried at 50° C.-70° C. for 4 h-6 h to obtain hybrid zirconium diboride whiskers.

6. The fluid loss reducer for drilling fluid according to claim 1, characterized in that: The initiator is benzoyl peroxide; the emulsifier includes Span-80 and Tween-60.

7. A method for preparing a fluid loss reducer for drilling fluid according to any one of claims 1 to 6, characterized in that: The following steps are involved: The phenolic composite crosslinking agent and the zirconium salt crosslinking agent are mixed and dissolved in water to obtain a crosslinking system; Dissolving acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N-vinyl pyrrolidone, and acryloyloxyethyltrimethylammonium chloride in water, and adjusting the pH to 7-8 to obtain a monomer mixed solution; Dissolve the emulsifier in the base oil, stir and mix to obtain a continuous phase; Adding the monomer mixed solution and the cross-linking system into the continuous phase, and obtaining an inverse emulsion after emulsification and dispersion; The reverse phase emulsion is stirred, and after heating, an inert gas is introduced to an oxygen-free state, an initiator is added, and a polymerization reaction is carried out to obtain a quaternary polymer emulsion; A polyvinyl alcohol aqueous solution is prepared; after surface activation treatment of hybrid zirconium diboride whiskers, the hybrid zirconium diboride whiskers are added to the polyvinyl alcohol aqueous solution together with the quaternary polymer emulsion, mixed, stirred to break the emulsion, and then dried to obtain a fluid loss reducer.

8. The method for preparing a fluid loss reducer for drilling fluid according to claim 7, characterized in that: The step of stirring the inverse emulsion, heating it, introducing an inert gas to an oxygen-free state, adding an initiator, and performing a polymerization reaction to obtain a quaternary polymer emulsion comprises: The reverse emulsion is stirred at a stirring rate of 80 r / min-120 r / min, and after the temperature is raised to 50° C.-75° C., an inert gas is introduced to an oxygen-free state, an initiator is added, and a polymerization reaction is carried out for 1 h-3 h to obtain a quaternary polymer emulsion.

9. The method for preparing a fluid loss reducer for drilling fluid according to claim 7, characterized in that: The step of performing surface activation treatment on the hybrid zirconium diboride whiskers comprises: The hybrid zirconium diboride whiskers are immersed in a hydrofluoric acid solution for 40-60 minutes, and then ultrasonically treated in a mixed solution of sodium hydroxide and polyvinyl pyrrolidone, with an ultrasonic frequency of 50 MHz-200 MHz and an ultrasonic time of 15-30 minutes, and then washed with anhydrous ethanol and deionized water for multiple times.

10. The method for preparing a fluid loss reducer for drilling fluid according to claim 7, characterized in that: The step of stirring and demulsifying comprises: The emulsion was broken by stirring at a stirring rate of 200 r / min-300 r / min, and after obtaining a solid product, it was transferred to anhydrous ethanol for shear washing for multiple times.